Pre- and post-embryogenesis of Rotylenchulus reniformis on castor: PRE- AND POST-EMBRYOGENESIS OF ROTYLENCHULUS RENIFORMIS ON CASTOR - SK MENAAZ FATHIMA; K SANKARI MEENA; P MANJU; B VIDYA SAGAR (Journal of Oilseeds Research, 2026)
The reniform nematode, Rotylenchulus reniformis, is a major constraint to oilseed production in India, particularly in castor. Understanding its developmental biology is essential for identifying vulnerable stages for effective management. The present study investigated the morphological and temporal progression of embryonic and post-embryonic development of R. reniformis under laboratory conditions. Embryogenesis was completed within 5-6 days, culminating in the emergence of second-stage juveniles (J2). Post-embryonic development through successive moults (J2-J4) resulted in adult formation within 26-29 days. Distinct morphological changes, including sexual differentiation at the third-stage juvenile (J3), were documented. The immature female was confirmed as the infective stage, attaining a reniform shape upon host establishment. These findings provide critical insights into the life cycle of R.reniformis, enabling improved timing of management interventions in castor-based cropping systems.